Método de reeducación sensitivo perceptivo motriz con uso del bosu como herramienta, aplicado en pacientes con esguince de tobillo en el Hospital Básico Militar No 11-BCB Galápagos, 2018 - Unach (2019)
The research entitled Sensitive Perceptive Motor Reeducation Method with the use of bosu as a tool, applied in patients with ankle sprain in the Military Basic Hospital No 11-BCB Galápagos 2018 "set the objective to determine the therapeutic effect of the Sensitive Motor Perceptual Reeducation Method with use of bosu as a tool to improve the function of injured structures in patients with ankle sprain. This method focuses on sensory stimulation to elicit motor responses and is aimed at the plasticity of nerve tissue and the relearning of movement. The level of research is exploratory, since it allowed to know the problem to specify the research, it is also descriptive because thanks to the information it was possible to know the therapeutic effects of the method in ankle sprains, it was evaluated with a Goniometric Test, the scale of Eva and the Daniels Test. The type of research is quantitative, by the data collected and statistical analysis by means of numerical evaluation. It was also documentary by the scientific and longitudinal evidence by the group of people with whom it was worked. The design of the research is field, since it was applied in the Basic Military Hospital No. 11 B.C.B Galápagos, where the problem of the area was analyzed and studied, finally the data were obtained. The method is bibliographical by the critical analysis of theories found in books, journals, articles and web documents, through the clinical histories data of the patients was obtained. The technique is of observation, since information was obtained that was later registered to perform critical and statistical analysis, by means of an evolution record. As an instrument, a kinetic evaluation sheet was applied according to the needs presented by the patients. The data was obtained by descriptive statistics, with Microsoft Excel and the SPSS software. The population in which the method was applied was twenty patients.